Personal Financial Planning from the Personality and Gender Perspective - Jumame, Santrinita (PT Global Digital Sains Tekno, 2023)
Financial planning is of concern to many researchers because this research can be a guide for realizing life goals, especially personal financial planning. This research aims to prove the influence of personality and gender on personal financial planning among students majoring in accounting at a private university. The type of research is quantitative research with primary data. Data was obtained by distributing questionnaires to accounting students in the Class of 2020 at a private university. Hypothesis testing is carried out using path analysis. The research results prove that personality influences financial planning, while financial planning cannot be differentiated between men and women (gender). Therefore, it is hoped that study programs and universities can provide outreach about financial planning tailored to students' personalities.